2015
DOI: 10.1007/s11118-015-9513-2
|View full text |Cite
|
Sign up to set email alerts
|

Phragmén-Lindelöf Theorems and p-harmonic Measures for Sets Near Low-dimensional Hyperplanes

Abstract: We prove estimates of a p-harmonic measure, p ∈ (n − m, ∞], for sets in R n which are close to an m-dimensional hyperplane Λ ⊂ R n , m ∈ [0, n − 1]. Using these estimates, we derive results of Phragmén-Lindelöf type in unbounded domains Ω ⊂ R n \ Λ for p-subharmonic functions. Moreover, we give local and global growth estimates for p-harmonic functions, vanishing on sets in R n , which are close to an m-dimensional hyperplane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
3
7
0
Order By: Relevance
“…Indeed, we conclude that solutions must vanish at the same rate as |x| k(v,p) as x approaches the apex (Corollary 5.1). Similar growth estimates where proved in the setting of C 1,1 -domains in [8] and for wider classes of equations and other geometric settings in [37,38,39,45,46,5,48]. An immediate consequence of Corollary 5.1 is the boundary Harnack inequality for p-harmonic functions in planar sectors, see (5.5).…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Indeed, we conclude that solutions must vanish at the same rate as |x| k(v,p) as x approaches the apex (Corollary 5.1). Similar growth estimates where proved in the setting of C 1,1 -domains in [8] and for wider classes of equations and other geometric settings in [37,38,39,45,46,5,48]. An immediate consequence of Corollary 5.1 is the boundary Harnack inequality for p-harmonic functions in planar sectors, see (5.5).…”
Section: Introductionsupporting
confidence: 58%
“…Estimates for the p-harmonic measure of a small spherical cap and of small axially symmetric sets are proved in [20,21], and in [22] estimates for the p-harmonic measure is given of the part of the boundary of an infinite slab outside a cylinder. In [46] estimates of p-harmonic measure, n − m < p ≤ ∞, for sets in R n which are close to an mdimensional hyperplane, 0 ≤ m ≤ n − 1 are proved, and in [42] it is proved that the p-harmonic measure in R n + of a ball of radius 0 < δ ≤ 1 in R n−1 is bounded above and below by a constant times δ α , and explicit estimates for α are given. For more on possible applications of p-harmonic measure see e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To mention previous results related to our boundary estimates for nonlinear PDEs, Aikawa-Kilpeläinen-Shanmugalingam-Zhong [2] proved similar results in the setting of positive pharmonic functions while in the same year Lewis-Nyström [15,16,17] started to develop a theory for proving boundary estimates such as the boundary Harnack inequality for p-Laplace type equations in more general geometries such as Lipschitz and Reifenberg-flat domains, and Lundström [18,19] estimated the growth of positive p-harmonic functions, n−m < p ≤ ∞, vanishing on an m-dimensional hyperplane in R n , 0 ≤ m ≤ n − 1. For nonhomogeneous equations Adamowicz-Lundström [1] proved similar boundary estimates as we do here but for positive p(x)-harmonic functions, and Avelin-Julin [3] proved a sharp boundary Harnack inequality for operators similar to those considered in this paper but without dependence on u.…”
Section: Introductionmentioning
confidence: 66%
“…Lindqvist [28] established Phragmén-Lindelöf's theorem for n-subharmonic functions when the boundary is an m-dimensional hyperplane in R n , 0 ≤ m ≤ n − 1. This was extended to p-subharmonic functions, n − m < p ≤ ∞, in Lundström [31]. We also mention that recently, Braga-Moreira showed that nonnegative solutions to a generalized p-Laplace equation in the upper halfplane, vanishing on {x n = 0}, equals u(x) = x n (modulo normalization) and Lundberg-Weitsman [29] studied the growth of solutions to the minimal surface equation over domains containing a halfplane.…”
Section: Introductionmentioning
confidence: 90%